Use of In Vivo and In Vitro Systems to Select Leishmania amazonensis Expressing Green Fluorescent Protein - Costa, Solange dos Santos; Golim, Marjorie de Assis; Rossi-Bergmann, Bartira [UNESP]; Maranhao Costa, Fabio Trindade; Giorgio, Selma (Korean Soc Parasitology, Seoul Natl Univ Coll Medi, 2011)
Various Leishmania species were engineered with green fluorescent protein (GFP) using episomal vectors that encoded an antibiotic resistance gene, such as aminoglycoside geneticin sulphate (G418). Most reports of GFP-Leishmania have used the flagellated extracellular promastigote, the stage of parasite detected in the midgut of the sandfly vector; fewer studies have been performed with amastigotes, the stage of parasite detected in mammals. In this study, comparisons were made regarding the efficiency for in vitro G418 selection of GFP-Leishmania amazonensis promastigotes and amastigotes and the use of in vivo G418 selection. The GFP-promastigotes retained episomal plasmid for a prolonged period and G418 treatment was necessary and efficient for in vitro selection. In contrast, GFP-amastigotes showed low retention of the episomal plasmid in the absence of G418 selection and low sensitivity to antibiotics in vitro. The use of protocols for G418 selection using infected BALB/c mice also indicated low sensitivity to antibiotics against amastigotes in cutaneous lesions.
Keywords: Leishmania amazonensis; green fluorescent protein; macrophage; geneticin